Ki Ratmiko Siswo Carito’s Shadow Puppet Art in Forming Islamic Cultural Identity in Banyumas, Central Java: Holistic-Integrative Fiqh Perspective - Hanif, Muh.; Karimah, Fatimah Azzahra; Suharto, Abdul Wachid Bambang; Adib, Shohibul (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2024)
The study on integrating shadow puppet art in the Islamic cultural landscape in Banyumas, Central Java, Indonesia, highlights the role of Ki Ratmiko Siswo Carito in cultural preservation and religious education. This paper aims to analyze how Ki Ratmiko Siswo Carito shaped Islamic culture through wayang art based on holistic, integrative jurisprudence. The method used in this paper is a literature study with a qualitative approach, which involves looking for written documents from books, articles, and other written documents that support the topic of discussion. The results showed that Ki Ratmiko Siswo Carito shapes Islamic cultural identity through meticulous puppet performances to convey Islamic teachings. The flexibility of puppets’ performances in incorporating Islamic values without losing their traditional essence reflects a successful model of cultural integration. It enriches the local cultural landscape and becomes a means of religious education, promoting the understanding and practice of Islam. Ki Ratmiko Siswo Carito’s dedication to preserving shadow puppet art with Islamic teachings significantly contributed to Banyumas’ Islamic cultural identity. Integrating Islamic values into shadow puppet art reflects the dynamic nature of cultural heritage and its potential as a medium for religious and cultural education.